THE EFFECT OF USING SEQUENCE PICTURE ON STUDENTS’ WRITING DESCRIPTIVE TEXT AT THE XI STUDENT OF SMA SWASTA KAMPUS PADANGSIDIMPUAN - Muhammad Rizwan Dalimunthe (JURNAL LINER (Language Intelligence and Educational Research), 2021)
ABSTRACT Dalimunthe, Rizwan. 2020. The Effect of Using Sequence Picture on Students' Writing Descriptive Text at the XI Students of SMA Swasta Kampus Padangsidimpuan. Thesis, English Department Program. South Tapanuli Institute of Education (IPTS). The purpose of this study was to find out: 1) to know the extent of using sequence picture on students 'writing descriptive text at the XI student of SMA Swasta Kampus Padangsidimpuan in 2020/2021 Academic Year, 2) to know the extent of the students' writing descriptive text before and after using sequence picture on students 'writing descriptive text at the XI student of SMA Swasta Kampus Padangsidimpuan in 2020/2021 Academic Year, 3) to find out whether there is any significant effect of using sequence picture on students' writing descriptive text at the XI student of SMA Swasta Kampus Padangsidimpuan in 2020/2021 Academic Year. The population of this study were all eleventh grade students of the Padangsidimpuan Campus Private High School, totaling 19 students. The research sample was XI IPA and XI IPS, which consist of 19 students who were taken by total sampling. The data collection technique used the observation sheet and composition test. The results of this study: 1) the application of the sequence picture in the "Good" category was 3.31. 2) the average score of the students' descriptive text writing ability was 46.85 in the "fail" category. Meanwhile, after using the sequence picture, 84.55 were categorized as "good". The results of data analysis show that the ttest is higher than ttest (ttest 100> ttable 27.77). So that the hypothesis is accepted. That is, there is a significant effect of sequence picture on the ability to write descriptive text of class XI students of the SMA Swasta Kampus Padangsidimpuan. Keywords: Sequence Picture, Writing Descriptive Text